(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This study titled "The Role of the Jordan Hashemite Charity Organization in Humanitarian Affairs in the Jordanian Arena (2008-2020)" aims to explore the organization, its definition, and its humanitarian role and contribution in mitigating and alleviating local impacts and risks